اختصاص القاضي الإداري في المنازعات العقارية - بليزاك السعيدي - عطابي مراد (جامعة المسيلة, 2025)
In view of the random exploitation and looting of real estate wealth, whether public or private, the Algerian legislator intervened to extend legal protection and put an end to the attacks on it, whether by individuals or the administration itself, by establishing legal rules and foundations aimed at regulating the exploitation and disposal of real estate. However, despite this, it still witnesses numerous attacks and disputes, the resolution of which is left to the administrative judiciary when the administration is a party to this dispute, which clarifies its role by imposing its oversight that ensures the embodiment of effective legal and judicial protection of real estate ownership, and thus achieving a balance between the public and private interest. This is embodied by virtue of the powers granted to it in the Civil and Administrative Procedures Law, as well as imposing its oversight over the procedures for the conduct of real estate lawsuits and its use of all means available to it, in order to investigate them until they are resolved. The aim of this study was to highlight the role of the administrative judge in protecting rights through his intervention in cases of administrative abuse, to identify the disputes within his jurisdiction, and to identify the role of the Algerian legislator in providing the administrative judge with the necessary means to perform his duties in settling real estate disputes, and the extent of the effectiveness of these means in enabling the administrative judge to achieve a balance between the disputing parties.
Keywords: words; Disputes; Administrative Judge; Cancellation Suit; Compensation; Expropriation